Análisis comparativo de la valoración de los activos biológicos bajo la NIC 41: estudio del sector avícola de la parroquia San Buenaventura de la ciudad de Latacunga. - Proaño Chuquitarco, Karina Elizabeth (2019)
In the present investigation, a comparative analysis of the biological assets valuation under IAS 41 for the poultry sector was developed considering two usual measurement bases: fair value and historical cost. It was carried out through the collection of information, using field, descriptive and bibliographic research through techniques such as: interview, observation and simulation of the process cost system. The Cobb broiler production is a permanent economic activity whose breeding process in the Sierra region meets the time of eight weeks from the acquisition until the chicken commercialization on foot, presenting the difficulty of valuing the biological asset in its different stages of fattening. Through this study, the standing stock was evaluated using two methods of measurement: fair value and historical cost, obtaining as a result of the chickens evaluation a positive difference of $ 435.10 when comparing the cost of production versus the active market of the chicken, production lot analyzed. Therefore, it is concluded that the best measurement basis for the broiler is the historical cost method because all the monetary expenses of the three cost elements involved in the chicken production process are recorded, providing a real, reliable result and technical; while the fair value through the active market is not feasible because reference prices are obtained only from the fattening stage ready for commercialization.